Selenium speciation in chicken breast samples from inorganic and organic selenium fed chickens using high performance liquid chromatography-inductively coupled plasma-mass spectrometry - Bakirdere, Sezgin; Volkan, Murvet; Ataman, O. Yavuz (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2018)
Speciation of selenium in chicken breast samples was performed by anion and cation exchange HPLC systems combined with ICP-MS. Samples were categorized into three groups consisting of Control Group, Inorganic Se Fed Group and Organic Se Fed Group. After the optimization of speciation parameters, selenomethionine, selenocystine, Se(IV) and Se(VI) were determined in the samples using the HPLC-ICP-MS system. Instrumental limit of detection values for selenium(IV), selenium(VI), Se in selenomethionine and Se in selenocystine were found to be 0.75, 0.80, 0.55 and 0.46 ng mL(-1), respectively. Protease XIV enzyme in 30.0 mM Tris HCl buffered to pH 7.2 was used in the extraction of selenium species from the sample matrix. Total selenium concentrations in the Control, Inorganic Se Fed and Organic Se Fed groups were found to be 675 +/- 85, 1084 +/- 198 and 887 +/- 139 ng g(-1) based on dry mass, respectively. The concentration of selenomethionine in the Organic Se Fed Group was found to be higher than those in the Control and Inorganic Se Fed Groups. Se(IV) was determined only in the Inorganic Se Fed Group.
Keywords: Food analysis; Selenium; Speciation; HPLC-ICP-MS; Chicken; Food composition; SE SPECIATION; EXTRACTION; SELENOMETHIONINE; SELENOCYSTEINE; CANCER; HEALTH; YEAST; Chemistry; Food Science & Technology